Political beliefs: Determinant well-being of the flood victims - Ayob, Noor Hadzlida; Sakdan, Mohd Fo'ad (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
The degree of well-being and satisfaction that people experienced has an influence on their political beliefs.During times such as in natural disasters or catastrophe, the victims’ senses of political beliefs are tested and can result in negative perceptions, a decline towards disbelief in their own politicians. However, during floods, the victims still seem to trust their own politicians.Although remedial strategies and relief may come from other parties, they still hold on to their political beliefs.Hence, this article attempts to investigate the political belief system of the flood victims and examine if it can indicate their political well-being